Chronic inflammation in psoriasis promotes visceral adipose tissue association with lipid-rich necrotic core through atherogenic myeloid score. (14th October 2021) - Manyak, G A; Patel, N H; Dey, A K; Svirydava, M; Parel, P; Teague, H L; Sorokin, A V; Teklu, M; Zhou, W; Rodante, J A; Keel, A; Playford, M P; et al.
Abstract: Background/Introduction: Psoriasis is a chronic inflammatory condition associated with adipose dysfunction and high-risk coronary artery disease features, including non-calcified coronary burden (NCB) and lipid-rich necrotic core (LRNC). Visceral adipose tissue (VAT) is a metabolically-active depot that secretes inflammatory and proatherogenic factors, and is associated with increased NCB. Additionally, an atherogenic myeloid score (AMS) comprised of classical monocytes, low-density granulocytes, and platelets was shown to associate with psoriasis severity and NCB. Purpose: To investigate the relationship between VAT and high-risk plaque features and test whether this relationship was potentially mediated by myeloid cells. Methods: A cohort of 131 psoriasis patients were included in this study. Atherogenic myeloid score components were calculated using complete blood count data (platelets) and by flow cytometry (monocytes, LDGs). Coronary NCB and LRNC were quantified using QAngio and vascuCAP respectively. VAT was defined as intra-abdominal fat and was quantified using an automated contouring software with abdominal CT scans. Statistical analyses were performed using STATA 12. Results: The cohort was middle-aged 50 (42–61) (median (IQR)), and predominantly male (61%). High VAT vs low VAT groups differed significantly in their NCB ((0.910±0.279) vs (1.431±0.517)); p<0.001), (mean ± SD). After adjustment for cardiovascular risk factors, VAT associated with the atherogenic myeloid score (β=0.221, p=0.044), with LRNC (β=0.128, p=0.047), and atherogenic myeloid score associated with LRNC (β=0.161, p=0.003). The relationship of VAT to LRNC was partially mediated by atherogenic myeloid score (25.14%, p=0.029) (Figure 1). Conclusions: VAT associated with LRNC, and this relationship was partially mediated by the atherogenic myeloid score. These findings suggest that bioactive VAT may impart risk on coronary artery disease in part through myeloid cells. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Heart, Lung, and Blood Institute Intramural Research Program in Bethesda, Maryland